(untitled) (Ustozlar uchun, 2024)
Abstract The article describes in detail the definition of the terms rights andfreedom, types of freedom, types of legal actions, legal literacy, the history of legal norms,constitutional guarantees of freedom, as well as digital innovative methods of freedomintegration in the field of rights and freedoms